2022
DOI: 10.3390/cancers14215431
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies in Advanced and Metastatic Urothelial Carcinoma

Abstract: This review describes the current landscape of targeted therapies in urothelial carcinoma. The standard of care for advanced urothelial carcinoma patients remains platinum-based combination chemotherapy followed by immunotherapy. However, median overall survival for these patients is still <1 year and there is an urgent need for alternative therapies. The advent of next-generation sequencing has allowed widespread comprehensive molecular characterization of urothelial tumors and, subsequently, the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In addition, exploring the potential of novel agents and combination therapies, especially in the context of drug resistance, is a critical area for future research. The development of therapies targeting specific molecular pathways implicated in bladder cancer progression, such as FGFR3 inhibitors and PARP inhibitors, holds promise for improving treatment outcomes ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, exploring the potential of novel agents and combination therapies, especially in the context of drug resistance, is a critical area for future research. The development of therapies targeting specific molecular pathways implicated in bladder cancer progression, such as FGFR3 inhibitors and PARP inhibitors, holds promise for improving treatment outcomes ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Advanced and metastatic UC account for the majority of deaths associated with this disease. 16 In a large retrospective study on metastatic upper UC, the most common site of metastasis was identified as the distant lymph nodes, and liver metastasis was found to be a poor prognostic factor, whereas primary tumour resection and chemotherapy were predictors of better survival outcome. 17 The development of cisplatin-based combination chemotherapy has extended median survival from several to 11–15 months.…”
Section: Discussionmentioning
confidence: 99%
“… 17 The development of cisplatin-based combination chemotherapy has extended median survival from several to 11–15 months. 16 However, the prognosis for metastatic patients with no response to primary chemotherapy is poor. 18 In addition, long term treatment with platinum may result in severe adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial cell carcinoma (UCC, formerly known as transitional cell carcinoma, TCC) is the most common neoplasm of the urinary system. UCC is the most common histologic type of BC and accounts for ~90% of all BC [1][2][3][4]. A number of histologic variants of UCC have been identified, including micropapillary, microcystic, nested, lymphoepitheliomalike, plasmacytoid, sarcomatoid, giant cell, poorly differentiated, lipid rich, clear cell and urothelial carcinoma with divergent differentiation.…”
Section: Introduction 1overviewmentioning
confidence: 99%
“…UCC is defined as the invasion of the cancer cells' basement membrane or lamina propria or deeper by neoplastic cells of urothelial origin. Invasion is defined as 'micro invasion' when the depth of invasion is 2 mm or less [2]. The World Health Organization (WHO) classifies BCs based on differentiation as low grade (grades 1 and 2) or high grade (grade 3) [1].…”
Section: Introduction 1overviewmentioning
confidence: 99%